Handbook of Contemporary Religion, Film, and Television - Cusack, Carole M.; Robertson, Venetia Laura Delano (Brill Handbooks on Contemporary Religion, 2026)
The Handbook of Contemporary Religion, Film, and Television contains twenty-three chapters on a variety of religions and religious phenomena, focusing on how they are depicted in film and television. Methodological considerations and academic debates concerning the effectiveness of popular cultural media in communicating information about religions and spiritualities are examined, and the films and television series are situated in political, social, geographical, and historical contexts. The authors are committed to open, serious, and scholarly work that accurately reflects the affective, entertainment, and imaginative dimensions of visual pop culture forms, while providing accurate and up to date information about the religious groups and trends they research.